2016
DOI: 10.5530/pc.2016.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Acai, cacao and maca extracts: Anticancer activity and growth inhibition of microbial triggers of selected autoimmune inflammatory diseases

Abstract: Background: The consumption of high antioxidant foods has been linked with a decreased incidence of some cancers and inflammatory diseases. Some high antioxidant foods also inhibit the growth of a variety of bacterial pathogens. Despite this, the high antioxidant 'superfoods' acai, cacao and maca are yet to be adequately tested for anticancer activity or the ability to inhibit the growth of bacterial triggers of autoimmune inflammatory diseases. Materials and Methods: Freeze dried acai, cacao and maca powders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similarly, Wright et al (2017) and Aldosary et al (2019) have demonstrated the effectiveness of different mountain pepper extracts against food-poisoning pathogens, such as C. perfringens [ 58 ] and Y. enterocolitica [ 23 ]. The anti-proliferative activity against these microorganisms could be explained by the combination of phenolic acids and flavonoids in the plant extracts, with flavonoids shielding lipids, proteins and DNA from oxidative damage [ 63 ]. However, further toxicological studies are required to verify the safety of these extracts before being considered for therapeutic uses.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Wright et al (2017) and Aldosary et al (2019) have demonstrated the effectiveness of different mountain pepper extracts against food-poisoning pathogens, such as C. perfringens [ 58 ] and Y. enterocolitica [ 23 ]. The anti-proliferative activity against these microorganisms could be explained by the combination of phenolic acids and flavonoids in the plant extracts, with flavonoids shielding lipids, proteins and DNA from oxidative damage [ 63 ]. However, further toxicological studies are required to verify the safety of these extracts before being considered for therapeutic uses.…”
Section: Resultsmentioning
confidence: 99%
“…A high number of different fatty acids were also found in the mixture which we suspect were obtained from the Acai Berry extract and separated into different molecules due to the preparation process. Although with moderate activity, Acai berry extract has been reported to exert an antibacterial effect against isolates of K. pneumoniae, Pseudomonas aeruginosa, and P. mirabilis [35]. The active components of ginger, zingerone, and zingiberene, were also detected by GC-MS. Al-Daihan et al (2013) showed that Zingeber officinale (Z. officinale), commonly known as ginger has a strong antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The Amazon açaí is widely consumed in Brazil but is already part of the eating habits of vast majority of the world's population. Its fruit exhibit pharmacological and medicinal properties mainly anticarcinogenic (Choi et al, 2017;Wang et al, 2016), anti-inflammatory (Favacho et al, 2011;Kang et al, 2011) Kang et al (2012 and antimicrobial (Shen et al, 2014;Belda-Galbis et al, 2015) activities. Amazon açaí, in addition to its nutritional qualities, is of great importance for the development of the Amazon region (Gordon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%